Nonlinear waves and offshore structures - Kim, Cheung Hun. (New Jersey : London : World Scientific, 2008)
Deals with analyses of nonlinear problems encountered in the design of offshore structures, as well as those that are of practical interest to ocean engineers and designers. This book presents conclusions drawn from research pertinent to nonlinear waves and their effects on the responses of offshore structures.
Includes bibliographical references (p. 499-506) and index.
Keywords: Nonlinear waves; Offshore structures -- Hydrodynamics -- Mathematical models; Offshore structures -- Design and construction -- Mathematical models; Ocean waves -- Mathematical models